Reactions from family of origin to the disclosure of lesbian motherhood via donor insemination. Issue 1 (2nd January 2020) - Alexandre Costa, Pedro; Tasker, Fiona; Anne Carneiro, Francis; Pereira, Henrique; Leal, Isabel
Abstract: Most studies of planned lesbian motherhood via donor insemination (DI) have sampled lesbian mothers in individualistic societies where adults have relatively distant connection to their family of origin. Our study examined the experiences of biological and non-biological lesbian mothers in five families who had children through DI after disclosing their motherhood status to their family networks in Portugal, a familistic society. The first theme identified by thematic analysis—"But why do you want to have a child?"—encapsulated the reactions of biological mothers' family of origin to the announcement of motherhood. Disclosure was mostly met by a shocked response in the family, rooted in the belief that lesbian women should not have children. The second theme—"But you weren't pregnant, how is this your child?"—summarized the reactions of non-biological mothers' family of origin to the disclosure of motherhood status as they considered refusing to recognize their grandchild in the absence of biological connection. Prejudice against lesbian-mother family formation was associated with the specific intersection of lesbianism and motherhood, but relationships between the mothers and their families were largely repaired because of familistic values.